Reading Habits, Economic Background, and Academic Achievement: A Moderation Study in Indonesian EFL Learners - Putra, Muhammad Lexmana; Munir, Ahmad; Masykuri, Edi Sunjayanto (English Department, Universitas Negeri Surabaya, 2025)
Reading habits are widely recognized as a key factor influencing students’ academic success, while socioeconomic background has often been associated with disparities in educational outcomes. However, limited research in the Indonesian EFL context has examined whether socioeconomic background moderates the effect of reading habits on academic achievement. This study employed a quantitative correlational design with moderation analysis to explore the relationship between reading habits, socioeconomic background, and English achievement among 155 twelfth-grade students at a private senior high school in Surabaya. Data were collected through questionnaires on reading habits and socioeconomic indicators, complemented by documentation of students’ final English scores. Statistical analysis involved descriptive statistics, Spearman correlation, multiple regression, and moderation testing. The findings showed that students’ reading habits were generally moderate, dominated by digital reading through social media, while academic reading remained limited. A significant positive correlation was found between reading habits and English achievement, indicating that stronger engagement with reading led to better performance. Socioeconomic background was positively associated with reading habits but did not directly predict academic achievement. Moreover, the moderation analysis revealed that socioeconomic background did not alter the relationship between reading habits and achievement. The study concludes that reading habits are a consistent and universal predictor of English academic achievement, regardless of socioeconomic differences. These results highlight the importance of fostering purposeful and sustained reading practices as a strategy to support equitable educational outcomes in Indonesia.